Research on the Volatility of RMB Exchange Rate Based on Time Series Analysis - Zhang, Xiaoyu (Transactions on Economics, Business and Management Research, 2024)
In recent years, with the rapid development of China’s national economy, more and more large-scale overseas transactions have become normalized, and the RMB exchange rate, as the foundation of foreign trade, has taken on increasingly important responsibilities. The RMB exchange rate is steadily advancing in market-oriented exploration, allowing the RMB to occupy an increasingly large proportion in international market transactions. Since 2020, the global economic situation has faced complex and severe challenges, and the fluctuation of the RMB exchange rate has become increasingly complex and frequent. Predicting the exchange rate can help us analyze the economic situation and prevent risks. This article selects the time series of China US exchange rates from November 1, 2017 to October 31, 2022 as the research object to construct different models. R language is used as the implementation software, and multiple models are horizontally compared. Finally, it is found that ARIMA-GARCH (1,1) is more suitable for short-term exchange rate prediction and has higher accuracy. Finally, this article also provides some suggestions for preventing exchange rate risks.